2020
DOI: 10.1007/s00330-020-07539-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial strain assessed by cardiovascular magnetic resonance feature tracking in healthy subjects—influence of segmentation and analysis software

Abstract: Objectives Quantification of myocardial deformation by feature tracking is of growing interest in cardiovascular magnetic resonance. It allows the assessment of regional myocardial function based on cine images. However, image acquisition, post-processing, and interpretation are not standardized. We aimed to assess the influence of segmentation procedure such as slice selection and different types of analysis software on values and quantification of myocardial strain in healthy adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…Contours were tracked automatically over the entire cardiac cycle to derive strain results [ 14 , 15 ]. For LV strain, segmentation was performed including the ventricular septum as previously established [ 16 , 17 ]. A less negative (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Contours were tracked automatically over the entire cardiac cycle to derive strain results [ 14 , 15 ]. For LV strain, segmentation was performed including the ventricular septum as previously established [ 16 , 17 ]. A less negative (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, although automated segmentation and motion tracking commercial software is available for cardiac cine imaging, manual correction of delineated contours used for tracking is often required, resulting in significant variations in strain depending on segmentation procedure and type of commercial software (15).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the open-source nature of the software enables the scientific community to easily apply our approach to other populations. Lastly, the purchase of commercially available software licenses whose accuracy depends on the segmentation procedure and vendor is not always an option for research groups ( 16 ), whereas open-source software provides key opportunities for cost reduction, clinical engagement in software development, and accelerated innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-automatic methods are available in commercial software. However, manual correction of tracked myocardial boundaries is still often required, which results in operator-related discrepancies in strain measures ( 16 ). Alternatively, we have shown that myocardial deformation can be automatically quantified from short-axis cine-MRI images using convolutional neural networks ( 17 ).…”
Section: Introductionmentioning
confidence: 99%